NEW INTERPRETATION OF CHINESE CLASSICS: «THE GREAT LEARNING» - Kanaev, Ilya (Revista Inclusiones, 2020)
This article introduces a new approach to the interpretation of Chinese classics by means of modern epistemology language. The introductory part reveals particular similarities of the Old Chinese grammar with the modern methods of the Activity Realism approach elaborated in the Theory of Knowledge. Its application to interpreting the classical canons of Chinese philosophy makes it possible to include them in contemporary interdisciplinary studies. The author’s translation of the Chinese classical text Da Xue, known as “The Great Learning” and included in the second part of the article serves to illustrate the practical application of the used method. The Great Learning was written by the first generation of Confucius students and became a part of the classical Confucian “Four books”. It was the basis for the imperial examination system in dynastic China and now it is among the first learning objects in the Chinese classical education system, Guo Xue. Chinese Culture has preserved its continuity for three thousand years and represents the most stable social system among the existing ones. Such longevity rests upon the classical texts. Their interpretation through the lens of the modern epistemology language can reveal new possibilities of contemporary scientific development, especially in considering the problems of human consciousness and social being. The English translation of “The Great Learning” presented in this article is devoted to the problems of rightful governance and reveals the interconnection between the personal development of the leader and his ability to guide the people.